Vibration-optimized design to improve safety related performance - Wohlgut, V.; Senner, V.; Carqueville, P.; Ellerböck, P.; Girardini, G. (10th International Congress on Science and Skiing, January 28 - February 1, 2025, Val di Fiemme, Italy, 2025)
INTRODUCTION: Vibration damping of sports equipment is nothing new. Over 45 years ago, the company Georg Fritzmeier GmbH & Co. KG, Großhelfendorf, Germany, presented the "Duo Ski". With the help of interchangeable weights - attached to the tip and tail of the ski - the vibration frequencies were adjusted [1]. Vibrations affect edge contact with the snow and, therefore, also the skier's control and safety [2]. Nowadays, the vibration characteristics of skis are influenced by a combination of materials with different internal damping. We use two essential pieces of ski mountaineering equipment, the ski and also the ice axe, to show how much vibrations can be influenced by material damping and weight adjustment to improve safety-related performance. While in skiing, the vibration is primarily induced by uneven ground, with an ice axe, the vibration is actively triggered by a strike from the athlete.